Breaking the Mirror: Alain Badiou’s Reading of Jacques Lacan - Ndiaye Berankova, Jana (Filozofski vestnik, 2024)
In this article, I focus on Alain Badiou’s idiosyncratic interpretation of Jacques Lacan and highlight his conceptual points of divergence with the psychoanalyst. I elaborate on Badiou’s distinction between philosophy, antiphilosophy, and sophistry as well as the notions of sense, ab-sense, and non-sense that he proposed in the book There’s No Such Thing as a Sexual Relationship: Two Lessons on Lacan as well as in his seminar on Lacan. Unlike Lacan, who affirmed that philosophy is subject to the fantasy of the One, Badiou claimed that the One exists merely as a result of an operation of counting. In this manner, he contested Lacan’s conviction that philosophy forecloses the real. I argue that Badiou’s main point of divergence with Lacan is centred on the notion of the subject and on the localization of the void in relation to the subject. I also touch upon philosophy’s relation to the symbolic, namely its ability to raise powerlessness to logical impossibility.